2012
DOI: 10.1104/pp.112.196048
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Small RNA-Mediated Responses to Cold Stress in a Wheat Thermosensitive Genic Male-Sterile Line by Deep Sequencing    

Abstract: The male sterility of thermosensitive genic male sterile (TGMS) lines of wheat (Triticum aestivum) is strictly controlled by temperature. The early phase of anther development is especially susceptible to cold stress. MicroRNAs (miRNAs) play an important role in plant development and in responses to environmental stress. In this study, deep sequencing of small RNA (smRNA) libraries obtained from spike tissues of the TGMS line under cold and control conditions identified a total of 78 unique miRNA sequences fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 101 publications
4
135
0
2
Order By: Relevance
“…[63] On the other hand, AP2 expression showed similar expression profile under cold and control conditions in wheat. [31] These data indicate that the detailed investigation on the role of AP2 under cold stress in tomato is needed.…”
Section: ããmentioning
confidence: 99%
See 4 more Smart Citations
“…[63] On the other hand, AP2 expression showed similar expression profile under cold and control conditions in wheat. [31] These data indicate that the detailed investigation on the role of AP2 under cold stress in tomato is needed.…”
Section: ããmentioning
confidence: 99%
“…[12] These proteins are auxin receptors that target repressors of ARF. [31] The different expression profiles of ARF6 and ARF8, and down regulation of TIR1 and F-box protein in cold-tolerant tomato cultivars suggested that auxin perception and signalling may change in stress conditions based on tolerance. In addition to miR167, there could be a key regulatory role of miR393 in the auxin-signalling pathway under cold stress in tomato.…”
Section: ããmentioning
confidence: 99%
See 3 more Smart Citations